Manajemen Anggaran Operasional dan Likuiditas: Pendekatan Anggaran Variabel, Piutang dan Kas - Ester Yohana Simanjuntak; Florentina Sitompul; Mohammad Idris (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of variable budgets, accounts receivable budgets, and cash budgets in supporting company operations and liquidity management. The research method employs a literature review by examining various journals and previous studies related to corporate budgeting. The results of the discussion indicate that variable budgets help companies control operating costs in line with activity levels. The accounts receivable budget plays a role in maintaining liquidity through the management of cash receipts and the monitoring of uncollectible accounts. Meanwhile, the cash budget serves as a tool for planning and controlling the company’s cash flow. These three budgets complement one another in improving operational efficiency, financial oversight, and management decision-making. Through the proper implementation of budgeting, companies can maintain financial stability and optimally support business continuity.